The Dual Income Tax and Firms' Income Shifting through the Choice of Organizational Form and Real Capital Investments - Annette Alstadsæter (Center for Economic Studies and ifo Institute (CESifo), 2003)
The dual income tax provides the self-employed entrepreneur with huge incentives to participate in tax minimizing income shifting to have more of his income taxed as capital income. The Norwegian split model is designed to remove these incentives, but it contains loopholes. The present paper concludes that the split model induces the self-employed entrepreneur to over-invest in firm real capital. In addition, the corporate organizational form serves as a tax shelter for high income entrepreneurs. The higher his income and the higher the difference between the marginal tax rates on labor and capital, the larger the incentives to incorporate.
Keywords: H24; H25; 330